A wear-resistant soft silicone composite material for blade welding and its preparation process

Through the modification and dispersion of carbon nanotubes and the coating of wear-resistant coating liquid, the problem of insufficient wear resistance of silicone materials during blade welding is solved, and the wear resistance and service life of the materials are significantly improved.

CN118667209BActive Publication Date: 2025-01-10JIANGXI XIRUI BLADE MANUFACTURING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411154916.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2025-01-10
Estimated Expiration
2044-08-22

AI Technical Summary

Technical Problem

The silicone materials used for welding existing blades have insufficient wear resistance, resulting in poor performance under high temperature and wear conditions.

Method used

Using carbon nanotube modification and dispersion technology and wear-resistant coating liquid, the material's wear-resistant performance is improved by applying wear-resistant coating on the surface of the silicone gasket. Specific steps include modification dispersion of carbon nanotubes, preparation and coating of preparation of blade welded silicone gaskets and wear-resistant coating liquid.

Benefits of technology

It significantly improves the wear resistance of silicone gaskets and enhances its service life and stability under high temperature and wear conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118667209B_ABST
    Figure CN118667209B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of polymer materials, and in particular to a wear-resistant soft silicone composite material for blade welding and a preparation process thereof. The preparation process comprises the following steps: modification and dispersion of carbon nanotubes; preparation of blade welding silicone gasket; preparation of wear-resistant coating liquid; and coating of wear-resistant coating on the surface of blade welding silicone gasket. The present invention will modify carbon nanotubes and prepare blade welding silicone gaskets through modified carbon nanotubes. The carbon nanotubes are modified because the slurry with carbon nanotubes has increased viscosity and the effect of ultrasonic dispersion is limited. The carbon nanotubes cannot be completely dispersed, resulting in uneven slurry. Therefore, the carbon nanotubes are modified so that the carbon nanotubes are not easy to agglomerate, which is conducive to the uniform distribution of carbon nanotubes in the slurry and the entanglement of carbon nanotubes in a small range, thereby increasing the viscosity of the slurry while maintaining the overall uniformity of the slurry, so that the gasket has good thermal conductivity and hardness during the blade welding process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a wear-resistant soft silica composite material for blade welding and a preparation process thereof. Background Art

[0002] Soft silicone is a very flexible and pliable silicone rubber material that is widely used in many industries due to its excellent physical properties and wide range of applications, such as being used as a gasket in blade welding. Soft silicone combines the inherent flexibility, chemical stability and biocompatibility of silicone, while also enhancing other properties by adding specific fillers or changing the formula.

[0003] In the prior art, the silicone used in blade welding mainly considers the thermal conductivity of silicone. Since a certain amount of heat will be generated during blade welding, there are certain requirements for the temperature resistance and heat resistance of the silicone material, while the wear resistance of the silicone material is less considered. In addition, soft silicone material is used in the blade welding process, and the soft silicone material wears more easily. Therefore, the present invention provides a soft silicone composite material with good wear resistance to solve the above problems. Summary of the invention

[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a wear-resistant soft silicone composite material for blade welding and a preparation process thereof.

[0005] A preparation process of a wear-resistant soft silicone composite material for blade welding, comprising the following steps:

[0006] S1: Carbon nanotube modified dispersion

[0007] Put carbon nanotubes in a reaction bottle and add ethanol, add water dispersant and n-decyltrimethoxysilane for ultrasonic treatment to obtain a treatment solution, dry the treatment solution, grind and sieve it to obtain treated carbon nanotubes, and store it for later use;

[0008] The specific steps include:

[0009] S1.1: First, take 5-8 parts by weight of carbon nanotubes into a reaction bottle and add 15-24 parts by weight of ethanol, and use a cell disruptor to sonicate for 1.5-2 hours;

[0010] S1.2: Then, 1.5-2 parts by weight of a water dispersant polyacrylic acid and 1.5-2 parts by weight of n-decyltrimethoxysilane are added and ultrasonically treated for 1-2 hours to obtain a treated solution;

[0011] S1.3: The treated solution is placed in an oven at 150-200°C and heated and dried for 1.5-2h, then ground through a 120-mesh sieve, and further heated and dried for 1-1.5h to obtain treated carbon nanotubes, which are then stored for later use;

[0012] S2: Preparation of blade-welded silicone gasket

[0013] S2.1: Weigh vinyl silicone oil, hydrogenated silicone oil, inhibitor and coupling agent vinyl tris(β-methoxyethoxy)silane in a volume ratio of 2:2:0.5:1 and mix in a reaction bottle, stirring for 5-10 minutes;

[0014] S2.2: Add 0.5% of the total mass of the platinum catalyst and 5% of the total mass of the treated spherical alumina to the reaction bottle, and continue stirring in the reaction bottle for 10 minutes;

[0015] S2.3: Add 2-3% of the total mass of the treated carbon nanotubes to the reaction bottle, form a slurry, and then perform ultrasonic treatment for 1-1.5 hours to obtain a preliminarily mixed mixture;

[0016] S2.4: Place the preliminarily mixed mixture on an open mixer and mix for 10-15 minutes until it is uniformly mixed;

[0017] S2.5: Take out the mixed material from the mixing mill and place it in a vacuum box at -100Mpa for 20-25min;

[0018] S2.6: Extruding the vacuumed mixed material into a fiber shape on a release film through a pipeline to obtain a fiber-shaped mixed material;

[0019] S2.7: Cut the fibrous mixture into sections and place them in a mold, compact them with a hot press, place the mold and the fibrous mixture together in a constant temperature oven at 150-160° C. for 2-2.5 hours to cure, and slice them to obtain blade-welded silicone gaskets;

[0020] S3: Wear-resistant coating liquid preparation

[0021] Weigh KH-560, MTES and nano-SiO2 sol and add them to a reaction bottle, stir magnetically and then heat to react to obtain a light white oily sol, then place the reaction bottle in an ice water bath to cool, stir rapidly during the cooling process, and while stirring, drop curing accelerator BMI into the reaction bottle, then add a mixed solvent and a curing agent into the reaction bottle to obtain a wear-resistant coating liquid for standby use;

[0022] S4: Apply a wear-resistant coating on the surface of the blade welded silicone gasket

[0023] The blade-welded silicone gasket was placed in a 0.5wt% NaOH solution, immersed in ultrasonic cleaning, then alternately cleaned with anhydrous ethanol and deionized water and dried to obtain the treated blade-welded silicone gasket. A wear-resistant coating droplet was dropped on the treated blade-welded silicone gasket, and a 10μm wire rod coater was used for scraping. After it was naturally leveled, it was placed in an oven for curing. After naturally cooling to room temperature, a wear-resistant soft silicone composite material for blade welding was obtained.

[0024] Furthermore, the preparation process of the treated spherical alumina in step S2.2 is as follows: take 5 μm spherical alumina and place it in a reaction bottle, add silane coupling agent and alcohol, the mass ratio of spherical alumina, silane coupling agent and alcohol is 1:4:10, initially stir with a glass rod for 5 minutes, stir with a magnetic stirrer at 200 r / min for 1 hour, clean with ultrasound for 6 hours and dry to obtain treated spherical alumina.

[0025] Furthermore, step S3, preparation of the wear-resistant coating liquid, comprises the following steps:

[0026] S3.1: Weigh 2-3 parts by mass of KH-560, 4.4-5 parts by mass of MTES and 3-8 parts by mass of nano-SiO2 sol and add them to a reaction bottle, and adjust the pH to 1-3 with a 10%wt hydrochloric acid aqueous solution;

[0027] S3.2: Stir magnetically in a water bath at 40-45°C for 2-2.5 hours, then raise the temperature to 80-85°C and continue the reaction for 1.5-2 hours to obtain a light white oily sol;

[0028] S3.3: Then, the reaction bottle is placed in an ice water bath and cooled to 4-10°C. During the cooling process, rapid stirring is performed at 500-600 r / min. While stirring, 5% of the total mass of the curing accelerator BMI is added dropwise to the reaction bottle, and the reaction is continued for 1-1.5 hours.

[0029] S3.4: Add 16-22 parts by mass of the mixed solvent to the reaction bottle, and then add 1-4 parts by mass of the curing agent, and react for 30-40 minutes to obtain the wear-resistant coating liquid for standby use.

[0030] Furthermore, the mixed solvent in step S3.4 is prepared by mixing methanol, ethanol, isopropanol and glycol methyl ether in a mass ratio of 5:13:8:1.

[0031] Furthermore, the curing agent in step S3.4 is aluminum acetylacetonate.

[0032] Further, step S4 is to coat the surface of the blade welding silicone gasket with a wear-resistant coating, comprising the following steps:

[0033] S4.1: Place the blade-welded silicone gasket in a 0.5wt% NaOH solution, soak for 1-1.5h, then ultrasonically clean for 30-40min, and then alternately clean with anhydrous ethanol and deionized water 2-3 times to remove surface impurities; finally, place in an oven at 80-90°C to dry, and obtain the treated blade-welded silicone gasket for later use;

[0034] S4.2: Take a drop of wear-resistant coating and apply it on the treated blade welding silicone gasket, and apply it with a 10μm wire rod coater. Place it in a ventilated place at room temperature for 30-35 minutes to allow it to level naturally; then place it in a 40-45℃ oven at a constant temperature for 30-35 minutes, then gradually increase the temperature to 80-85℃, and cure at a constant temperature for 2.5-3h. After naturally cooling to room temperature, the wear-resistant soft silicone composite material for blade welding is obtained.

[0035] A wear-resistant soft silicone composite material for blade welding is prepared by the preparation process of the wear-resistant soft silicone composite material for blade welding.

[0036] Compared with the prior art, the present invention has at least the following beneficial effects:

[0037] 1. The present invention will modify carbon nanotubes and prepare blade welding silicone gaskets through the modified carbon nanotubes. The addition of carbon nanotubes and their entanglement in the slurry greatly increases the viscosity of the slurry. The carbon nanotubes are modified because the slurry with the addition of carbon nanotubes has increased viscosity, and the effect of ultrasonic dispersion is limited. The carbon nanotubes cannot be completely dispersed, resulting in uneven slurry. Therefore, the carbon nanotubes are modified to make them less likely to agglomerate, which is beneficial to the uniform distribution of the carbon nanotubes in the slurry and their entanglement in a small range, thereby maintaining the overall uniformity of the slurry while increasing the viscosity of the slurry.

[0038] 2. The present invention prepares a wear-resistant coating liquid and coats the wear-resistant coating liquid on the surface of the gasket to obtain a wear-resistant soft silicone composite material for blade welding. The main components of the prepared wear-resistant coating include silicone and silicon dioxide. Silicon dioxide can improve the wear resistance, and the coating whose main component is silicone can be well combined with the gasket after coating. In subsequent use, due to friction and pressure, the coating and the gasket are more easily combined with each other due to their similar materials, and the two will not be separated, thereby improving the wear resistance of the composite material.

[0039] 3. The present invention pre-treats the gasket to remove stains on the gasket surface that have not been removed during the preparation and storage process, and then coats the gasket to ensure that there is no foreign matter between the coating and the gasket, thereby improving the bonding strength between the coating and the gasket. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.

[0041] Figure 1 This is a process flow chart of preparing a wear-resistant soft silicone composite material used in blade welding according to an embodiment of the present invention. DETAILED DESCRIPTION

[0042] The following is a detailed description of a wear-resistant soft silicone composite material for blade welding and its preparation process provided by the present invention in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.

[0043] Embodiment 1:

[0044] A preparation process of a wear-resistant soft silicone composite material for blade welding, such as Figure 1 As shown, the following steps are included:

[0045] S1: Carbon nanotube modified dispersion

[0046] S1.1: First, take 5 parts by mass of carbon nanotubes into a reaction bottle and add 15 parts by mass of ethanol, and use a cell disruptor to sonicate for 2 hours;

[0047] S1.2: Then, 1.5 parts by weight of a water dispersant polyacrylic acid and 1.5 parts by weight of n-decyltrimethoxysilane were added and ultrasonically treated for 2 hours to obtain a treated solution;

[0048] S1.3: The treated liquid is placed in an oven at 150° C. and heated and dried for 2 h, then ground through a 120-mesh sieve, and further heated and dried for 1 h to obtain treated carbon nanotubes, which are then stored for later use.

[0049] S2: Preparation of blade-welded silicone gasket

[0050] S2.1: Weigh vinyl silicone oil, hydrogenated silicone oil, inhibitor and coupling agent vinyl tris(β-methoxyethoxy)silane in a volume ratio of 2:2:0.5:1 and mix in a reaction bottle, stirring for 5 min;

[0051] S2.2: Add 0.5% of the total mass of the platinum catalyst and 5% of the total mass of the treated spherical alumina to the reaction bottle, and continue stirring in the reaction bottle for 10 minutes;

[0052] S2.3: Add 2% of the total mass of the treated carbon nanotubes to the reaction bottle, form a slurry, and then perform ultrasonic treatment for 1 hour to obtain a preliminarily mixed mixture;

[0053] S2.4: Place the preliminarily mixed mixture on an open mixer and mix for 10 minutes until it is uniformly mixed;

[0054] S2.5: Take out the mixed material from the mixing mill and place it in a vacuum box at -100Mpa for 20 minutes;

[0055] S2.6: Extruding the vacuumed mixed material into a fiber shape on a release film through a pipeline to obtain a fiber-shaped mixed material;

[0056] S2.7: Cut the fibrous mixture into sections and place them in a mold, compact them with a hot press, place the mold and the fibrous mixture together in a constant temperature oven at 150°C for 2 hours to solidify, and slice them to obtain blade-welded silicone gaskets.

[0057] The preparation process of treated spherical alumina is as follows: take 5μm spherical alumina and place it in a reaction bottle, add silane coupling agent and alcohol, the mass ratio of spherical alumina, silane coupling agent and alcohol is 1:4:10, stir it with a glass rod for 5 minutes, stir it with a magnetic stirrer at 200r / min for 1 hour, clean it with ultrasound for 6 hours and dry it to obtain treated spherical alumina.

[0058] S3: Wear-resistant coating liquid preparation

[0059] S3.1: Weigh 2 parts by mass of KH-560 (KH-560 silane coupling agent, γ-glycidyloxypropyltrimethoxysilane), 4.4 parts by mass of MTES (methyltriethoxysilane) and 3 parts by mass of nano-SiO2 sol and add them into a reaction bottle, and adjust the pH to 1 with a 10%wt hydrochloric acid aqueous solution;

[0060] S3.2: Stir magnetically in a water bath at 40°C for 2 h, then raise the temperature to 80°C and continue the reaction for 2 h to obtain a light white oily sol;

[0061] S3.3: The reaction bottle was then placed in an ice water bath and cooled to 4°C. During the cooling process, rapid stirring was performed at 500 r / min. While stirring, 5% of the total mass of the system as curing accelerator BMI (bismaleimide) was added dropwise to the reaction bottle. The reaction was continued for 1 hour.

[0062] S3.4: Add 16 parts by mass of a mixed solvent into the reaction bottle. The mixed solvent is methanol, ethanol, isopropanol and glycol methyl ether mixed in a mass ratio of 5:13:8:1. Then add 1 part by mass of a curing agent aluminum acetylacetonate and react for 30 minutes to obtain a wear-resistant coating liquid for use.

[0063] S4: Apply a wear-resistant coating on the surface of the blade welded silicone gasket

[0064] S4.1: Place the blade-welded silicone gasket in a 0.5wt% NaOH solution, soak for 1 hour, then ultrasonically clean for 30 minutes, and then clean it three times with anhydrous ethanol and deionized water alternately to remove surface impurities; finally, dry it in an oven at 80°C for later use;

[0065] S4.2: Take a drop of wear-resistant coating and apply it on the treated blade welding silicone gasket, and apply it with a 10μm wire rod coater. Place it in a ventilated place at room temperature for 30 minutes to allow it to level naturally; then put it in a 40℃ oven at a constant temperature for 30 minutes, then gradually increase the temperature to 80℃ and cure at a constant temperature for 3 hours. After naturally cooling to room temperature, the wear-resistant soft silicone composite material for blade welding is obtained.

[0066] Embodiment 2:

[0067] A preparation process of a wear-resistant soft silicone composite material for blade welding, such as Figure 1 As shown, the following steps are included:

[0068] S1: Carbon nanotube modified dispersion

[0069] S1.1: First, take 8 parts by mass of carbon nanotubes into a reaction bottle and add 24 parts by mass of ethanol, and use a cell disruptor to sonicate for 2 hours;

[0070] S1.2: Then, 2 parts by weight of water dispersant polyacrylic acid and 2 parts by weight of n-decyltrimethoxysilane were added and ultrasonically treated for 2 hours to obtain a treated solution;

[0071] S1.3: The treated liquid is placed in an oven at 150° C. and heated and dried for 2 h, then ground through a 120-mesh sieve, and further heated and dried for 1 h to obtain treated carbon nanotubes, which are then stored for later use.

[0072] S2: Preparation of blade-welded silicone gasket

[0073] S2.1: Weigh vinyl silicone oil, hydrogenated silicone oil, inhibitor and coupling agent vinyl tris(β-methoxyethoxy)silane in a volume ratio of 2:2:0.5:1 and mix in a reaction bottle, stirring for 5 min;

[0074] S2.2: Add 0.5% of the total mass of the platinum catalyst and 5% of the total mass of the treated spherical alumina to the reaction bottle, and continue stirring in the reaction bottle for 10 minutes;

[0075] S2.3: Add 3% of the total mass of the treated carbon nanotubes to the reaction bottle, form a slurry, and then perform ultrasonic treatment for 1 hour to obtain a preliminarily mixed mixture;

[0076] S2.4: Place the preliminarily mixed mixture on an open mixer and mix for 10 minutes until it is uniformly mixed;

[0077] S2.5: Take out the mixed material from the mixing mill and place it in a vacuum box at -100Mpa for 20 minutes;

[0078] S2.6: Extruding the vacuumed mixed material into a fiber shape on a release film through a pipeline to obtain a fiber-shaped mixed material;

[0079] S2.7: Cut the fibrous mixture into sections and place them in a mold, compact them with a hot press, place the mold and the fibrous mixture together in a constant temperature oven at 150°C for 2 hours to solidify, and slice them to obtain blade-welded silicone gaskets.

[0080] The preparation process of treated spherical alumina is as follows: take 5μm spherical alumina and place it in a reaction bottle, add silane coupling agent and alcohol, the mass ratio of spherical alumina, silane coupling agent and alcohol is 1:4:10, stir it with a glass rod for 5 minutes, stir it with a magnetic stirrer at 200r / min for 1 hour, clean it with ultrasound for 6 hours and dry it to obtain treated spherical alumina.

[0081] S3: Wear-resistant coating liquid preparation

[0082] S3.1: Weigh 3 parts by mass of KH-560 (KH-560 silane coupling agent, γ-glycidyloxypropyltrimethoxysilane), 5 parts by mass of MTES (methyltriethoxysilane) and 8 parts by mass of nano-SiO2 sol and add them to a reaction bottle, and adjust the pH to 1 with a 10%wt hydrochloric acid aqueous solution;

[0083] S3.2: Stir magnetically in a water bath at 40°C for 2 h, then raise the temperature to 80°C and continue the reaction for 2 h to obtain a light white oily sol;

[0084] S3.3: The reaction bottle was then placed in an ice water bath and cooled to 4°C. During the cooling process, rapid stirring was performed at 500 r / min. While stirring, 5% of the total mass of the system as curing accelerator BMI (bismaleimide) was added dropwise to the reaction bottle. The reaction was continued for 1 hour.

[0085] S3.4: Add 22 parts by mass of a mixed solvent to the reaction bottle. The mixed solvent is methanol, ethanol, isopropanol and glycol methyl ether mixed in a mass ratio of 5:13:8:1. Then add 4 parts by mass of a curing agent aluminum acetylacetonate and react for 30 minutes to obtain a wear-resistant coating liquid for use.

[0086] S4: Apply a wear-resistant coating on the surface of the blade welded silicone gasket

[0087] S4.1: Place the blade-welded silicone gasket in a 0.5wt% NaOH solution, soak for 1 hour, then ultrasonically clean for 30 minutes, and then clean it three times with anhydrous ethanol and deionized water alternately to remove surface impurities; finally, dry it in an oven at 80°C for later use;

[0088] S4.2: Take a drop of wear-resistant coating and apply it on the treated blade welding silicone gasket, and apply it with a 10μm wire rod coater. Place it in a ventilated place at room temperature for 30 minutes to allow it to level naturally; then put it in a 40℃ oven at a constant temperature for 30 minutes, then gradually increase the temperature to 80℃ and cure at a constant temperature for 3 hours. After naturally cooling to room temperature, the wear-resistant soft silicone composite material for blade welding is obtained.

[0089] Embodiment 3:

[0090] A preparation process of a wear-resistant soft silicone composite material for blade welding, such as Figure 1 As shown, the following steps are included:

[0091] S1: Carbon nanotube modified dispersion

[0092] S1.1: First, take 5 parts by weight of carbon nanotubes into a reaction bottle and add 15 parts by weight of ethanol, and use a cell disruptor to sonicate for 1.5 hours;

[0093] S1.2: Then, 1.5 parts by weight of a water dispersant polyacrylic acid and 1.5 parts by weight of n-decyltrimethoxysilane were added and ultrasonically treated for 1 hour to obtain a treated solution;

[0094] S1.3: The treated liquid is placed in an oven at 200° C. and heated and dried for 1.5 h, then ground through a 120-mesh sieve, and further heated and dried for 1.5 h to obtain treated carbon nanotubes, which are then stored for later use.

[0095] S2: Preparation of blade-welded silicone gasket

[0096] S2.1: Weigh vinyl silicone oil, hydrogenated silicone oil, inhibitor and coupling agent vinyl tris(β-methoxyethoxy)silane in a volume ratio of 2:2:0.5:1 and mix in a reaction bottle, stirring for 10 min;

[0097] S2.2: Add 0.5% of the total mass of the platinum catalyst and 5% of the total mass of the treated spherical alumina to the reaction bottle, and continue stirring in the reaction bottle for 10 minutes;

[0098] S2.3: Add 2% of the total mass of the treated carbon nanotubes to the reaction bottle to form a slurry and then perform ultrasonic treatment for 1.5 hours to obtain a preliminarily mixed mixture;

[0099] S2.4: Place the preliminarily mixed mixture on an open mixer and mix for 15 minutes until it is uniformly mixed;

[0100] S2.5: Take out the mixed material from the mixing mill and place it in a vacuum box at -100Mpa for 25 minutes;

[0101] S2.6: Extruding the vacuumed mixed material into a fiber shape on a release film through a pipeline to obtain a fiber-shaped mixed material;

[0102] S2.7: Cut the fibrous mixture into sections and place them in a mold, and compact them with a hot press. Place the mold and the fibrous mixture together in a constant temperature oven at 160°C for 2.5 hours to cure, and slice them to obtain blade-welded silicone gaskets.

[0103] The preparation process of treated spherical alumina is as follows: take 5μm spherical alumina and place it in a reaction bottle, add silane coupling agent and alcohol, the mass ratio of spherical alumina, silane coupling agent and alcohol is 1:4:10, stir it with a glass rod for 5 minutes, stir it with a magnetic stirrer at 200r / min for 1 hour, clean it with ultrasound for 6 hours and dry it to obtain treated spherical alumina.

[0104] S3: Wear-resistant coating liquid preparation

[0105] S3.1: Weigh 2 parts by mass of KH-560 (KH-560 silane coupling agent, γ-glycidyloxypropyltrimethoxysilane), 4.4 parts by mass of MTES (methyltriethoxysilane) and 3 parts by mass of nano-SiO2 sol and add them to a reaction bottle, and adjust the pH to 3 with a 10%wt hydrochloric acid aqueous solution;

[0106] S3.2: Magnetic stirring was carried out in a water bath at 45°C for 2.5 h, then the temperature was raised to 85°C and the reaction was continued for 1.5 h to obtain a light white oily sol;

[0107] S3.3: The reaction bottle was then placed in an ice water bath and cooled to 10°C. During the cooling process, rapid stirring was performed at 600 r / min. While stirring, 5% of the total mass of the system as curing accelerator BMI (bismaleimide) was added dropwise to the reaction bottle. The reaction was continued for 1.5 hours.

[0108] S3.4: Add 16 parts by mass of a mixed solvent into the reaction bottle. The mixed solvent is methanol, ethanol, isopropanol and glycol methyl ether mixed in a mass ratio of 5:13:8:1. Then add 1 part by mass of a curing agent aluminum acetylacetonate and react for 40 minutes to obtain a wear-resistant coating liquid for use.

[0109] S4: Apply a wear-resistant coating on the surface of the blade welded silicone gasket

[0110] S4.1: Place the blade-welded silicone gasket in a 0.5wt% NaOH solution, soak for 1 hour, then ultrasonically clean for 30 minutes, and then clean twice with anhydrous ethanol and deionized water alternately to remove surface impurities; finally, place in a 90°C oven to dry for later use;

[0111] S4.2: Take a drop of wear-resistant coating and apply it on the treated blade welding silicone gasket, and apply it with a 10μm wire rod coater. Place it in a ventilated place at room temperature for 30 minutes to allow it to level naturally; then put it in a 45℃ oven at a constant temperature for 35 minutes, then gradually increase the temperature to 85℃ and cure at a constant temperature for 2.5 hours. After naturally cooling to room temperature, the wear-resistant soft silicone composite material for blade welding is obtained.

[0112] Comparative Example 1:

[0113] Compared with Example 1, the difference of Comparative Example 1 is that step S1 is not performed, and carbon nanotubes are directly added in step S2, specifically, “S2.1: weigh vinyl silicone oil, hydrogen-containing silicone oil, inhibitor and coupling agent vinyl tris (β-methoxyethoxy) silane in a volume ratio of 2:2:0.5:1, mix in a reaction bottle, and stir for 5 minutes;

[0114] S2.2: Add 0.5% of the total mass of the platinum catalyst and 5% of the total mass of the treated spherical alumina to the reaction bottle, and continue stirring in the reaction bottle for 10 minutes;

[0115] S2.3: Add 2% of the total mass of carbon nanotubes to the reaction bottle, form a slurry, and then perform ultrasonic treatment for 1 hour to obtain a preliminarily mixed mixture;

[0116] S2.4: Place the preliminarily mixed mixture on an open mixer and mix for 10 minutes until it is uniformly mixed;

[0117] S2.5: Take out the mixed material from the mixing mill and place it in a vacuum box at -100Mpa for 20 minutes;

[0118] S2.6: Extruding the vacuumed mixed material into a fiber shape on a release film through a pipeline to obtain a fiber-shaped mixed material;

[0119] S2.7: Cut the fibrous mixture into sections and place them in a mold, compact them with a hot press, place the mold and the fibrous mixture together in a constant temperature oven at 150°C for 2 hours to solidify, and slice them to obtain a blade-welded silicone gasket. The prepared wear-resistant soft silicone composite material for blade welding is recorded as Comparative Example 1.

[0120] Comparative Example 2:

[0121] Compared with Example 1, the difference of Comparative Example 2 is that no carbon nanotubes are added in step S2, specifically: “S2.1: weigh vinyl silicone oil, hydrogen-containing silicone oil, inhibitor and coupling agent vinyl tris (β-methoxyethoxy) silane in a volume ratio of 2:2:0.5:1, mix in a reaction bottle, and stir for 5 minutes;

[0122] S2.2: Add 0.5% of the total mass of the platinum catalyst and 5% of the total mass of the treated spherical alumina to the reaction bottle, and continue stirring in the reaction bottle for 10 minutes;

[0123] S2.3: Ultrasonicate for another 1 h to obtain a preliminarily mixed mixture;

[0124] S2.4: Place the preliminarily mixed mixture on an open mixer and mix for 10 minutes until it is uniformly mixed;

[0125] S2.5: Take out the mixed material from the mixing mill and place it in a vacuum box at -100Mpa for 20 minutes;

[0126] S2.6: Extruding the vacuumed mixed material into a fiber shape on a release film through a pipeline to obtain a fiber-shaped mixed material;

[0127] S2.7: Cut the fibrous mixture into sections and place them in a mold, compact them with a hot press, place the mold and the fibrous mixture together in a constant temperature oven at 150°C for 2 hours to solidify, and slice them to obtain a blade-welded silicone gasket. The prepared wear-resistant soft silicone composite material for blade welding is recorded as Comparative Example 2.

[0128] Comparative Example 3:

[0129] Compared with Example 1, the difference of Comparative Example 3 is that step S3 is not performed, and a commercially available epoxy resin coating agent is used in step S4 instead of the wear-resistant coating liquid prepared in step S3, specifically: "S4.1: Put the blade welding silicone gasket into a NaOH solution with a concentration of 0.5wt%, soak for 1 hour, then ultrasonically clean for 30 minutes, and then wash it alternately with anhydrous ethanol and deionized water for 3 times to remove surface impurities; finally, place it in an oven at 80°C for drying and set aside;

[0130] S4.2: Take a commercially available epoxy resin coating agent and drop it on the treated blade welding silicone gasket, and apply it with a 10μm wire rod coater. Place it in a ventilated place at room temperature for 30 minutes to allow it to level naturally; then put it in a 40°C oven at a constant temperature for 30 minutes, then gradually increase the temperature to 80°C, and cure at a constant temperature for 3 hours. After naturally cooling to room temperature, a wear-resistant soft silicone composite material for blade welding is obtained. The prepared wear-resistant soft silicone composite material for blade welding is recorded as Comparative Example 3.

[0131] The viscosity of the preliminarily mixed mixtures obtained in step S2.3 of Examples 1-3 and Comparative Examples 1-2 was tested using a rotational viscometer, as shown in Table 1.

[0132] Table 1

[0133]

[0134] It can be seen that the viscosity of Example 1 is 9813 mPa·s, the viscosity of Example 2 is 9806 mPa·s, and the viscosity of Example 3 is 9801 mPa·s. The difference between the three is small and can be regarded as allowed within the error range. The viscosity of Comparative Example 1 is 8945 mPa·s. It can be seen that the viscosity of Comparative Example 1 in which the carbon nanotubes are not modified is lower than that of the mixture with modified nanotubes due to the uneven dispersion of carbon nanotubes. The viscosity of Comparative Example 2 is 8266 mPa·s, indicating that the viscosity of the mixture will be significantly reduced without the addition of carbon nanotubes.

[0135] Coating wear resistance test

[0136] A 600-mesh sandpaper loaded with a 500-g weight was evenly rubbed 100 times at a constant speed in Examples 1-3 and Comparative Examples 1-3. The dust on the surface was blown away with an ear bulb every 10 times. The mass of the substrate was weighed and the abrasion weight loss was calculated, as shown in Table 2.

[0137] Table 2

[0138]

[0139] It can be seen from the data in the table that the weight loss of Example 1 in 100 frictions is the lowest, while the difference between Example 2 and Example 3 and Example 1 is not much, and the final 100 friction weight losses are 5.89 mg, 5.99 mg and 5.94 mg respectively.

[0140] The weight loss of comparative example 1 after abrasion is greater than that of the embodiment, and the weight loss after 100 abrasions is 8.06 mg. It can be seen that the modified carbon nanotubes can make the mixture more uniform, thus affecting the wear resistance of the material. The weight loss after 100 abrasions of comparative example 2 is 8.21 mg, while the weight loss after 20 abrasions of comparative example 2 is 1.76 mg, and that of comparative example 1 is 1.89 mg. This may be because the uniformity of the material after adding carbon nanotubes to comparative example 1 is not as good as that of comparative example 2, resulting in a higher initial weight loss after abrasion than that of comparative example 2. However, carbon nanotubes provide certain wear resistance, and the weight loss after 100 abrasions can be regarded as the overall weight loss after abrasion. Therefore, in terms of weight loss after 100 abrasions, comparative example 2 is more than comparative example 1.

[0141] The weight loss after 20 abrasions of Comparative Example 3 is 2.16 mg, and the weight loss after 100 abrasions is 10.69 mg. It can be seen that the wear-resistant coating liquid prepared by the present invention has better wear resistance than the commercially available epoxy resin coating liquid.

[0142] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A process for preparing a wear-resistant soft silicone composite material for blade welding, characterized in that: The steps include: S1: Carbon nanotube modified dispersion Put carbon nanotubes in a reaction bottle and add ethanol, add water dispersant and n-decyltrimethoxysilane for ultrasonic treatment to obtain a treatment solution, dry the treatment solution, grind and sieve it to obtain treated carbon nanotubes, and store it for later use; The specific steps include: S1.1: First, take 5-8 parts by weight of carbon nanotubes into a reaction bottle and add 15-24 parts by weight of ethanol, and use a cell disruptor to sonicate for 1.5-2 hours; S1.2: Then, 1.5-2 parts by weight of a water dispersant polyacrylic acid and 1.5-2 parts by weight of n-decyltrimethoxysilane are added and ultrasonically treated for 1-2 hours to obtain a treated solution; S1.3: The treated solution is placed in an oven at 150-200°C and heated and dried for 1.5-2h, then ground through a 120-mesh sieve, and further heated and dried for 1-1.5h to obtain treated carbon nanotubes, which are then stored for later use; S2: Preparation of blade-welded silicone gasket S2.1: Weigh vinyl silicone oil, hydrogenated silicone oil, inhibitor and coupling agent vinyl tris(β-methoxyethoxy)silane in a volume ratio of 2:2:0.5:1 and mix in a reaction bottle, stirring for 5-10 minutes; S2.2: Add 0.5% of the total mass of the platinum catalyst and 5% of the total mass of the treated spherical alumina to the reaction bottle, and continue stirring in the reaction bottle for 10 minutes; S2.3: Add 2-3% of the total mass of the treated carbon nanotubes to the reaction bottle, form a slurry, and then perform ultrasonic treatment for 1-1.5 hours to obtain a preliminarily mixed mixture; S2.4: Place the preliminarily mixed mixture on an open mixer and mix for 10-15 minutes until it is uniformly mixed; S2.5: Take out the mixed material from the mixing mill and place it in a vacuum box at -100Mpa for 20-25min; S2.6: Extruding the vacuumed mixed material into a fiber shape on a release film through a pipeline to obtain a fiber-shaped mixed material; S2.7: Cut the fibrous mixture into sections and place them in a mold, compact them with a hot press, place the mold and the fibrous mixture together in a constant temperature oven at 150-160° C. for 2-2.5 hours to cure, and slice them to obtain blade-welded silicone gaskets; S3: Wear-resistant coating liquid preparation S3.1: Weigh 2-3 parts by mass of KH-560, 4.4-5 parts by mass of MTES and 3-8 parts by mass of nano-SiO2 sol and add them to a reaction bottle, and adjust the pH to 1-3 with a 10%wt hydrochloric acid aqueous solution; S3.2: Stir magnetically in a water bath at 40-45°C for 2-2.5 hours, then raise the temperature to 80-85°C and continue the reaction for 1.5-2 hours to obtain a light white oily sol; S3.3: Then, the reaction bottle is placed in an ice water bath and cooled to 4-10°C. During the cooling process, rapid stirring is performed at 500-600 r / min. While stirring, 5% of the total mass of the curing accelerator BMI is added dropwise to the reaction bottle, and the reaction is continued for 1-1.5 hours. S3.4: Add 20-25 parts by weight of the mixed solvent to the reaction bottle, and then add 0.5-1 parts by weight of the curing agent, and react for 30-40 minutes to obtain the wear-resistant coating liquid for standby use; S4: Apply a wear-resistant coating on the surface of the blade welded silicone gasket S4.1: Place the blade-welded silicone gasket in a 0.5wt% NaOH solution, soak for 1-1.5h, then ultrasonically clean for 30-40min, and then alternately clean with anhydrous ethanol and deionized water 2-3 times to remove surface impurities; finally, place in an oven at 80-90°C to dry, and obtain the treated blade-welded silicone gasket for later use; S4.2: Take a drop of wear-resistant coating and apply it on the treated blade welding silicone gasket, and apply it with a 10μm wire rod coater. Place it in a ventilated place at room temperature for 30-35 minutes to allow it to level naturally; then place it in a 40-45℃ oven at a constant temperature for 30-35 minutes, then gradually increase the temperature to 80-85℃, and cure at a constant temperature for 2.5-3h. After naturally cooling to room temperature, the wear-resistant soft silicone composite material for blade welding is obtained.

2. The preparation process of the wear-resistant soft silicone composite material for blade welding according to claim 1, characterized in that: The preparation process of the treated spherical alumina in step S2.2 is as follows: take 5μm spherical alumina and place it in a reaction bottle, add silane coupling agent and alcohol, the mass ratio of spherical alumina, silane coupling agent and alcohol is 1:4:10, stir initially with a glass rod for 5 minutes, stir with a magnetic stirrer at 200r / min for 1 hour, clean and dry by ultrasound for 6 hours to obtain treated spherical alumina.

3. The preparation process of the wear-resistant soft silicone composite material for blade welding according to claim 2, characterized in that: The mixed solvent in step S3.4 is prepared by mixing methanol, ethanol, isopropanol and glycol methyl ether in a mass ratio of 5:13:8:

1.

4. The process for preparing a wear-resistant soft silicone composite material for blade welding according to claim 3, characterized in that: The curing agent in step S3.4 is aluminum acetylacetonate.

5. A wear-resistant soft silicone composite material for blade welding, characterized in that: The composite material is prepared by the preparation process of the wear-resistant soft silicone composite material for blade welding as described in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Heat-resistant high-strength shape memory polyurethane elastomer and preparation method thereof

    CN112062928A

  • High-thermal-conductivity insulating silica gel gasket and preparation method thereof

    CN112457673A